Gula Tebu Saka: Industri Tebu Rakyat di Nagari Bukik Batabuah, Kecamatan Canduang, Kabupaten Agam (1975-2021) - Novitri, Sherly; Midawati, Midawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2024)
This study discusses about the saka sugarcane, like history, sugarcane plantations, and the impact of history of sugar cane industry to people in Nagari Bukik Batabuah District. The research for this thesis employs historical research methods with a socio-economic perspective. The research encompasses four stages: heuristics, source criticism, interpretation, and historiography. Sugarcane plantations have been an enduring tradition passed down through generations. The processing of sugarcane into sugar saka has become a daily routine for the people of Nagari Bukik Batabuah. Since 1975, traditional methods involving buffalo power for sugarcane grinding were still in use. However, in 2010, technological advancements led to increased production, impacting farmers' incomes and subsequently bringing about socio-economic changes within Nagari Bukik Batabuah.